Pengaruh Perbedaan Lama Waktu Perendaman Bubu Lipat terhadap Hasil Tangkapan Rajungan (Portunus pelagicus) di Perairan Kuala Penet, Lampung Timur - Keegan Irfano Imam; Kusyairi Achmad; Saraswati Exist (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
This study aims to analyze the effect of combining bait types and immersion durations on the catch yields of blue swimming crabs (Portunus pelagicus) in the waters of Kuala Penet, East Lampung. The research method employed was a field experiment utilizing a factorial Completely Randomized Design (CRD). The focus of the study was directed toward two types of bait, namely goldstripe sardine (Sardinella spp.) and chicken intestines, with three variations of immersion duration: 6 hours, 12 hours, 18 hours, and 24 hours. Through statistical analysis, it was discovered that the combination of goldstripe sardine bait and a 6-hour immersion duration provided the most optimal catch yields. Nevertheless, chicken intestines demonstrated strong potential as an economical and sustainable alternative bait at a 12-hour immersion duration. The interaction between the bait type and immersion duration variables proved to be significant, thereby supporting an integrated approach to the management of collapsible pots. These findings provide a scientific basis for formulating sustainable crab fishing guidelines that can be adopted by local fishermen and relevant authorities to support the ecosystem-based conservation of coastal fishery resources in East Lampung.